2010
DOI: 10.1186/1465-9921-11-127
|View full text |Cite
|
Sign up to set email alerts
|

Ovalbumin sensitization and challenge increases the number of lung cells possessing a mesenchymal stromal cell phenotype

Abstract: BackgroundRecent studies have indicated the presence of multipotent mesenchymal stromal cells (MSCs) in human lung diseases. Excess airway smooth muscle, myofibroblasts and activated fibroblasts have each been noted in asthma, suggesting that mesenchymal progenitor cells play a role in asthma pathogenesis. We therefore sought to determine whether MSCs are present in the lungs of ovalbumin (OVA)-sensitized and challenged mice, a model of allergic airways disease.MethodsBalb/c mice were sensitized and challenged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 58 publications
(74 reference statements)
1
35
0
Order By: Relevance
“…While not well understood, both smooth muscle hypertrophy and hyperplasia contribute to increased muscle mass in airway disease (1). A recent study of an airway sensitization and challenge model in mice found specific evidence for smooth muscle hypertrophy, measuring increases in SMC size that were comparable to those recorded here (2). Similar studies in rats showed decreased expression of key smooth muscle markers (21), implying that hypertrophy is associated with decreased density of expression in multiple systems.…”
Section: Discussionsupporting
confidence: 63%
“…While not well understood, both smooth muscle hypertrophy and hyperplasia contribute to increased muscle mass in airway disease (1). A recent study of an airway sensitization and challenge model in mice found specific evidence for smooth muscle hypertrophy, measuring increases in SMC size that were comparable to those recorded here (2). Similar studies in rats showed decreased expression of key smooth muscle markers (21), implying that hypertrophy is associated with decreased density of expression in multiple systems.…”
Section: Discussionsupporting
confidence: 63%
“…Slides were probed with FITC-or Cy3-labeled mouse anti-␣-smooth muscle actin (clone 1A4, Sigma-Aldrich), AlexaFluorconjugated rabbit anti-phospho-GSK-3␀/mouse anti-␀-catenin (Cell Signaling Technology, Beverly, MA), or rabbit anti-connective tissue growth factor (CTGF) (Abcam, Cambridge, MA). Primary antibodies were coupled to AlexaFluor dyes (Invitrogen, Carlsbad, CA) as described (5).…”
Section: Methodsmentioning
confidence: 99%
“…It is possible to speculate that resistin plays a significant role in bone marrow proliferation and homeostasis. Interestingly, Bentley et al [33] showed that the number of multipotent mesenchymal stromal cells increased in the lungs of mice subjected to an ovalbumin-induced asthma model. It is also known that RELMa expression is highly upregulated in mouse lungs when subjected to that asthma model [2].…”
mentioning
confidence: 99%